Experience of nature and times of silence as a resource to cope with the COVID-19 pandemic and their effects on psychological wellbeing—Findings from a continuous cross-sectional survey in Germany - Büssing, Arndt; Recchia, Daniela Rodrigues; Baumann, Klaus (Frontiers in Public Health, 2022)
Background: The COVID-19 pandemic with its lockdowns affected social relations and mental health conditions of people worldwide. We aimed to analyze the relevance of nature and times of silence as resources to cope with the pandemic. Of interest was how experiences of nature and times of silence are related to wondering awe and gratitude and psychological wellbeing, and how these have changed during the different phases of the pandemic. Finally, we asked whether Nature/Silence would mediate the link between Awe/Gratitude and wellbeing. Methods: Cross-sectional survey with standardized questionnaires (i.e., PCQ, GrAw-7, BMLSS-10, WHO-5) enrolling participants during the different phases of the COVID-19 pandemic. The total sample of 5,155 participants from Germany consisted of 65% women and 34% men, with a mean age of 45.0 ± 14.0 years. Results: Directly after the first lock down, Nature/Silence and Awe/Gratitude scores were high, and decreased along with wellbeing with the onset of the second lockdown in winter 2020, while perceived burden constantly increased. Nature/Silence was rated lowest by people with reduced wellbeing (Eta2 = 0.058) and feeling lonely or socially isolated (Eta2 = .042). Predictor analyses revealed that wellbeing as dependent variable was predicted best by corona related perception of burden, Awe/Gratitude, reflection of life, Nature/Silence, and further by perceived changes in terms of relationships and spirituality (R2=.55). In mediation analyses Awe/Gratitude proved to be a significant predictor for Nature/Silence (β=0.55, p< 0.0001) and of wellbeing (β=0.05, p< 0.0001). The mediation analysis explained 37% of the variability in the data. The direct influence of Awe/Gratitude on wellbeing was estimated as β=0.09 (p< 0.0001), and the mediation effect of Nature/Silence on the link between Awe/Gratitude and wellbeing was significant, too (β=0.03, p < 0.0001), explaining 25% of the total effect. Conclusions: Nature/Silence and Awe/Gratitude were used as relevant resources during the pandemic, although they cannot fully buffer the negative effects of the social restrictions that resulted in decreases of wellbeing and increases of perceived burden. Perception of nature as a sensitizer of positive experiences particularly during difficult phases of life could be trained to stabilize wellbeing and thus to contribute to public health.